Substance use among persons with homeless experience in primary care. Issue 4 (1st October 2016) - Stringfellow, Erin J.; Kim, Theresa W.; Gordon, Adam J.; Pollio, David E.; Grucza, Richard A.; Austin, Erika L.; Johnson, N. Kay; Kertesz, Stefan G.
ABSTRACT: Background: Community survey data suggest high prevalence of substance use disorders among currently homeless individuals. There are less data regarding illicit drug and alcohol use problems of homeless-experienced persons engaged in primary care. They may have less severe use and require different care responses from primary care teams. Methods: The authors surveyed currently and formerly homeless, i.e., homeless-experienced, persons engaged in primary care at five federally funded programs in the United States, administering the World Health Organization (WHO) Alcohol, Smoking and Substance Involvement Screening Test (ASSIST). The ASSIST definitions of lower, moderate, and high risk were used to assess a spectrum of lifetime and recent substance use, from any use to likely dependence, and to identify sociodemographic and health status characteristics associated with severity of use. Results: Almost one half of the sample ( N = 601) had recently (within the past three months) used alcohol, and one third had recently used an illicit drug. The most commonly used illicit drugs in the past three months were cannabis (19%), cocaine (16%), and opioids (7.5%). Over one half (59%) of respondents had ASSIST-defined moderate- or high-risk substance use. A significant proportion (31%) of those identified as at moderate risk had no recent substance use, but did report past problematic use. Ten percent of the lower-risk group had past problematic use of alcohol. Severity of use was associated with worse health status, but not with housing status or type of homelessness experienced. Conclusions: Less severe (moderate-risk) use and past problematic use, potentially indicative of remitted substance use disorders, were more common than high-risk use in this primary care, homeless-experienced sample. These findings highlight the urgency of identifying effective ways to reduce risky substance use and prevent relapse in homeless-experienced persons.